A three-dimensional spacer fabric reinforced composite material and a preparation method and application thereof

CN117328272BActive Publication Date: 2026-11-03XI'AN POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311351122.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2026-11-03
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

现有三维编织复合材料的吸波性能较差,且在第三个维度上力学性能薄弱,难以实现介电性能的多层梯度设计。

Method used

A three-dimensional prefabricated weaving method was adopted, which controlled the fiber arrangement in the structure by weaving a mixture of conductive and insulating fiber yarns, and combined with an absorbent in the resin matrix to prepare a three-dimensional spacer fabric reinforced composite material.

Benefits of technology

It achieves excellent wave absorption performance, mechanical properties in three dimensions, anti-delamination ability, light weight, simple manufacturing process, and low cost, making it suitable for aerospace, transportation, and electronic construction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117328272B_ABST
    Figure CN117328272B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and discloses a three-dimensional spacer fabric reinforced composite material, a preparation method and application thereof, the preparation method comprising: three-dimensional preform weaving: regularly arranging yarns to prepare three-dimensional preforms with different parameters and different cross-sectional shapes; curing: coating a resin matrix on the three-dimensional preforms, and curing to form a three-dimensional spacer fabric reinforced composite material. The three-dimensional spacer fabric reinforced composite material prepared by the present application controls the wave-absorbing performance of the material by designing a three-dimensional structure and controlling the arrangement of conductive fibers in the structure. The arrangement of the conductive fibers presents a circuit resonance, and thus the material has good wave-absorbing performance. The present application is used for preparing stealth components in the fields of military and national defense, aerospace, transportation or electronic building.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material technology, specifically relating to a three-dimensional spacer fabric reinforced composite material, its preparation method, and its application. Background Technology

[0002] Traditional molding processes for resin-based composite materials include hand lay-up, lamination, and resin transfer molding. Fabric-reinforced composite materials prepared using two-dimensional lamination processes exhibit high specific strength and specific modulus, and the resulting resin-based composite materials possess advantages such as lightweight and good mechanical properties. High-performance fiber-reinforced composite materials, such as carbon fiber-reinforced resin-based composites and quartz fiber-reinforced resin-based composites, are widely used in aerospace, construction, transportation, and electronics. With the increasingly widespread application of electromagnetic waves in various fields, the requirements for weaponry and equipment are also becoming more stringent. The preparation of structural-functional integrated composite materials can not only achieve good stealth effects but also reduce weight; therefore, structural microwave absorbing composite materials have received widespread attention both domestically and internationally.

[0003] Laminated composites easily achieve a layered gradient distribution of dielectric constant, resulting in good microwave absorption performance. However, because laminated composites lack continuous fiber reinforcement in the third dimension, their mechanical properties in this direction are weakened due to the presence of layers, limiting their applications. Three-dimensional reinforced composites exhibit good mechanical properties in all three dimensions, but limitations in fabrication methods make it difficult to achieve a multi-layered gradient design of dielectric properties. Currently, the microwave absorption performance of three-dimensional braided composites is relatively poor. Therefore, developing a three-dimensional braided composite material with excellent microwave absorption performance is urgently needed and essential. Summary of the Invention

[0004] This invention provides a three-dimensional spacer fabric reinforced composite material, its preparation method, and its application, which solves the problem that the microwave absorption performance of three-dimensional braided composite materials prepared by existing technologies is relatively poor.

[0005] A method for preparing a three-dimensional spacer fabric reinforced composite material specifically includes the following steps:

[0006] Weaving of three-dimensional preforms: Yarns are arranged in a regular pattern to produce three-dimensional preforms with different parameters and cross-sectional shapes;

[0007] Curing: The resin matrix is ​​coated onto the three-dimensional preform and cured to obtain a three-dimensional spacer fabric reinforced composite material.

[0008] Preferably, in the weaving of the three-dimensional preform, the yarn is woven from a mixture of conductive and insulating fiber yarns.

[0009] Preferably, in the weaving of the three-dimensional preform, the parameters include: the thickness of the conductive fiber bundles, the spacing between them, the direction of their arrangement, the tilt angle between the core layer and the surface layer, and the number of layers in the three-dimensional preform.

[0010] Preferably, the diameter of the conductive fiber bundle is 0.1 to 3.5 cm;

[0011] The arrangement spacing is as follows: in the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1 to 3.5 cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1 to 3.5 cm between adjacent conductive fiber yarns.

[0012] The arrangement direction can be a single X direction, a single Y direction, or a combination of both X and Y directions.

[0013] Preferably, the tilt angle between the core layer and the surface layer is 30 to 90°.

[0014] Preferably, the three-dimensional prefabricated body has 1 to 5 layers.

[0015] Preferably, the cross-sectional shape is triangular, rectangular, or trapezoidal.

[0016] Preferably, during curing, the resin matrix is ​​filled with an absorbent, which is a lightweight carbon-based absorbent.

[0017] The second objective of this invention is to protect the three-dimensional spacer fabric reinforced composite material obtained by the aforementioned preparation method.

[0018] A third objective of this invention is to protect the application of the aforementioned three-dimensional spacer fabric reinforced composite material in the fabrication of stealth components in the fields of military defense, aerospace, transportation, or electronic construction.

[0019] Compared with the prior art, the beneficial effects of the present invention are:

[0020] 1. The three-dimensional spacer fabric-reinforced composite material prepared by this invention controls the wave absorption performance of the material by designing the three-dimensional structure and controlling the arrangement of conductive fibers within the structure. The arrangement of the conductive fibers exhibits circuit resonance. According to transmission line theory, when a transmission line changes periodically, there will be additional energy loss at the periodic discontinuities. When the wavelength of the electromagnetic wave is equal to half an integer multiple of the period length, the energy loss is the greatest, which manifests as resonance in the insertion loss. This converts the electromagnetic wave into energy loss, thus exhibiting excellent wave absorption performance.

[0021] 2. The three-dimensional spacer fabric reinforced composite material prepared by the present invention can regulate the wave absorption performance through the synergistic effect of the three-dimensional preform and the absorbent in the matrix.

[0022] 3. The present invention uses a three-dimensional fabric structure to prepare a three-dimensional spacer fabric-reinforced microwave absorbing composite material. There are fabric connecting layers in all three dimensions. Therefore, in addition to having microwave absorbing and stealth functions, it also has anti-delamination ability and good mechanical properties in all three dimensions.

[0023] 4. The three-dimensional spacer fabric reinforced composite material prepared by this invention has the property of being lightweight.

[0024] 5. The three-dimensional spacer fabric-reinforced microwave absorbing composite material prepared by this invention adopts a hand lay-up process, which can effectively control the uniformity and flowability of the resin on the preform. The preparation process is simple and low in cost.

[0025] 6. The three-dimensional spacer fabric-reinforced microwave absorbing composite material prepared by this invention has the characteristics of adjustable microwave absorption performance and good mechanical properties in all three dimensions. It can be widely used in aerospace, transportation, construction, and electronics industries. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the single-layer three-dimensional spacer fabric composite material prepared in Example 1;

[0027] Figure 2 The reflectance curves of the composite material prepared in Example 1 in the 8-18 GHz range;

[0028] Figure 3 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 1 in the 8-18 GHz range, with the front side facing upwards;

[0029] Figure 4 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 1 in the range of 8-18 GHz with the reverse side facing up;

[0030] Figure 5 The reflectance curve of the composite material prepared in Example 2 in the 8-18 GHz range;

[0031] Figure 6 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 2 in the 8-18 GHz range, with the front side facing upwards;

[0032] Figure 7 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 2 with the reverse side facing up in the 8-18 GHz range;

[0033] Figure 8 This is a schematic diagram of the double-layer three-dimensional spacer fabric composite material prepared in Example 3;

[0034] Figure 9The reflectance curve of the composite material prepared in Example 3 in the 8-18 GHz range;

[0035] Figure 10 The reflection coefficient and absorption coefficient curves of the composite material prepared in Example 3 in the 8-18 GHz range with the front side facing upwards;

[0036] Figure 11 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 3 in the range of 8-18 GHz with the reverse side facing up;

[0037] Figure 12 The reflectance curve of the composite material prepared in Example 4 in the 8-18 GHz range;

[0038] Figure 13 The reflection coefficient and absorption coefficient curves of the composite material prepared in Example 4 in the 8-18 GHz range when the front is facing upwards;

[0039] Figure 14 The curves of the reflection coefficient and absorption coefficient of the composite material prepared in Example 4 in the 8-18 GHz range with the reverse side facing up;

[0040] Figure 15 The reflectance curves of the composite material prepared for Comparative Example 1 in the 8-18 GHz range;

[0041] Figure 16 The curves of the reflection coefficient and absorption coefficient of the composite material prepared for Comparative Example 1 in the range of 8-18 GHz;

[0042] Figure 17 This is a schematic diagram of Comparative Example 5 when the cross-sectional shape is triangular. Detailed Implementation

[0043] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0044] Example 1

[0045] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared. It was a single layer with a filament bundle width of 0.5 cm.

[0046] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, which in turn connects to the warp roller to prevent the warp yarn from breaking due to the impact force of the heddles. Since the weaving structure is a three-dimensional spaced structure, the middle layer has a larger yarn feed than the upper and lower layers. Therefore, the middle layer and the upper and lower layers of warp yarn cannot use the same warp roller. Secondly, the humidity should be maintained at 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The size of the woven sample is 18cm×18cm, and the cross-sectional shape is one of triangle, rectangle or trapezoid. In this embodiment, the cross-sectional shape is selected as triangle. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The width of the conductor fiber bundle is 0.5cm. The fiber arrangement is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1 cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1 cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 30°. The lower layer of the three-dimensional preform does not contain conductive carbon fibers. During testing, the side of the upper layer containing conductive carbon fibers facing upwards is defined as the front (Z), and the side of the lower layer without conductive carbon fibers facing upwards is defined as the back (F).

[0047] (2) Preparation of epoxy resin: The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model: ZTJ-03AB. The epoxy resin and matching curing agent were prepared in a ratio of 3:1. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After it was evenly mixed, it was placed in a vacuum oven to remove air bubbles from the mixture and allowed to stand for 30 minutes to avoid uneven coating caused by air bubbles.

[0048] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber by hand lay-up and then supported. In this embodiment, metal pads are used for support. The thickness of the metal pads is 1cm, so that the fabric maintains its three-dimensional shape after exiting the oven.

[0049] (4) Curing: Place the preform with the matrix solution evenly coated in it in a DZ-2BCIV vacuum drying oven and dry it at 70℃ for 10 hours. The resulting three-dimensional spacer fabric reinforced composite material is shown below. Figure 1 , Figure 1To obtain a single-layer three-dimensional spacer fabric composite material with electromagnetic absorption properties, white fibers are insulating fibers and black fibers are conductive fibers. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are flipped to ensure uniform resin content on both surfaces. The composite material is then weighed and cut for testing.

[0050] (5) The volume fraction of the fiber in the prepared composite material was 45%. The reflectance curve of the composite material in the 8-18 GHz range was tested using the bow method, as shown in the figure. Figure 2 As shown, during the test, the side of the upper layer containing conductive carbon fibers facing upwards is defined as the front (Z), and the side of the lower layer without conductive carbon fibers facing upwards is defined as the back (F). The reflection coefficient and absorption coefficient of the composite material when the front side faces upwards are as follows: Figure 3 As shown, Γ-Z represents the reflectance when the front side is facing up, and AZ represents the absorption coefficient when the front side is facing up; the reflectance and absorption coefficients of the composite material when the back side is facing up are shown in the figure. Figure 4 As shown, Γ-F represents the reflection coefficient with the reverse side facing upwards, and AF represents the absorption coefficient with the reverse side facing upwards. The flat compression properties of the composite material were tested according to GB / T1453-2005, with a test size of 65mm × 65mm, and the measured flat compression load was 1502N. The three-point bending properties of the composite material were tested according to standard GB / T1456-2005, with a span of 100mm. The maximum bending load in the warp direction was 122N, and the maximum bending load in the weft direction was 250N.

[0051] Example 2

[0052] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared. It was a single layer with a filament bundle width of 1 cm.

[0053] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, which in turn connects to the warp roller to avoid the warp yarn breaking due to the impact force of the heddles. Since the weaving structure is a three-dimensional spaced structure, the middle layer has a larger yarn feed than the upper and lower layers. Therefore, the middle layer and the upper and lower warp yarns cannot use the same warp roller. Secondly, the humidity should be maintained at 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The size of the woven sample is 18cm×18cm, and the cross-sectional shape is triangular. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The width of the conductor fiber bundle is 1cm, and the inclination angle between the core layer and the surface layer is 60°. The arrangement spacing is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 1.5 cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 1.5 cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 60°. The lower layer of the three-dimensional preform does not contain conductive carbon fibers. During testing, the side of the upper layer containing conductive carbon fibers facing upwards is defined as the front (Z), and the side of the lower layer without conductive carbon fibers facing upwards is defined as the back (F).

[0054] (2) Preparation of epoxy resin: The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model: ZTJ-03AB. The epoxy resin and matching curing agent were prepared in a ratio of 3:1. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After it was evenly mixed, it was placed in a vacuum oven to remove air bubbles from the mixture and allowed to stand for 30 minutes to avoid uneven coating caused by air bubbles.

[0055] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber and supported. In this embodiment, metal pads are used for support. The thickness of the metal pads is 1cm, so that the fabric maintains its three-dimensional shape after exiting the oven.

[0056] (4) Curing: The preform with the matrix solution evenly coated is placed in a DZ-2BCIV vacuum drying oven and dried at 70℃ for 10 hours to obtain a three-dimensional spacer fabric reinforced composite material. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are reversed to ensure that the resin content on the top and bottom surfaces is uniform. The composite material is then weighed and cut for testing.

[0057] (5) The volume fraction of the fiber in the prepared composite material is 50%. The reflectance curve of the composite material in the 8-18 GHz range was tested using the bow method, as shown in the figure. Figure 5 As shown, the reflection coefficient and absorption coefficient of the composite material when the front side faces upwards are as follows: Figure 6 As shown, Γ-Z represents the reflectance when the front side is facing up, and AZ represents the absorption coefficient when the front side is facing up; the reflectance and absorption coefficients of the composite material when the back side is facing up are shown in the figure. Figure 7 As shown, Γ-F represents the reflection coefficient when the reverse side is facing up, and AF represents the absorption coefficient when the reverse side is facing up.

[0058] Example 3

[0059] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared, consisting of two layers.

[0060] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, and the guide wire is connected to the warp roller chain to avoid the warp yarn breaking due to the impact force of the heddles. For a three-dimensional spaced fabric with a double-layer cross-section, there are three face layers and two core layers. The middle layer has a larger yarn feed than the upper and lower layers. Therefore, the warp yarns of the middle layer and the upper and lower layers cannot use the same warp roller. Secondly, the humidity should be kept within the range of 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The size of the woven sample is 18cm×18cm, and the cross-section is a double-layer triangle. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The arrangement spacing is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 2.5cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 2.5cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 60°.

[0061] (2) Preparation of epoxy resin: The epoxy resin and matching curing agent were prepared in a 3:1 ratio. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After uniform mixing, the mixture was placed in a vacuum oven to remove air bubbles and allowed to stand for 30 minutes to prevent uneven coating caused by air bubbles. The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model ZTJ-03AB.

[0062] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber, and a 1cm thick metal block is used as support so that the fabric maintains its three-dimensional shape after exiting the oven.

[0063] (4) Curing: Place the preform with the matrix solution evenly coated in it in a DZ-2BCIV vacuum drying oven and dry it at 70℃ for 10 hours. The resulting three-dimensional spacer fabric reinforced composite material is shown below. Figure 8 During the curing process, 0.5 hours after curing begins, the top and bottom surfaces of the composite material are reversed to ensure uniform resin content on both surfaces. The composite material is then weighed and cut for testing. Figure 8 The resulting double-layer three-dimensional spacer fabric composite material with electromagnetic absorption properties is described, wherein the white fibers are insulating fibers and the black fibers are conductive fibers.

[0064] (5) The volume fraction of the fiber in the prepared composite material is 55%. The reflectance curve of the composite material in the 8-18 GHz range was tested using the bow method, as shown in the figure. Figure 9 As shown, the reflection coefficient and absorption coefficient of the composite material when the front side faces upwards are as follows: Figure 10 As shown, the reflection coefficient and absorption coefficient of the composite material with the reverse side facing up are as follows: Figure 11 As shown, Γ-F represents the reflection coefficient when the reverse side is facing up, and AF represents the absorption coefficient when the reverse side is facing up.

[0065] Example 4

[0066] A single-layer, three-dimensional spacer fabric-reinforced composite material with a rectangular cross-section and wave-absorbing properties was prepared.

[0067] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, which in turn connects to the warp roller to avoid the warp yarn breaking due to the impact force of the heddles. Since the weaving structure is a three-dimensional spaced structure, the middle layer has a larger yarn feed than the upper and lower layers. Therefore, the warp yarns of the middle layer and the upper and lower layers cannot use the same warp roller. Secondly, the humidity should be maintained at 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The woven sample size is 18cm×18cm, and the cross-sectional shape is rectangular. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The arrangement spacing is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 3.5 cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 3.5 cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 60°. No conductive carbon fiber is placed in the lower layer of the three-dimensional preform.

[0068] (2) Preparation of epoxy resin: The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model: ZTJ-03AB. The epoxy resin and matching curing agent were mixed at a ratio of 3:1. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After uniform mixing, the mixture was placed in a vacuum oven to remove air bubbles and allowed to stand for 30 minutes to prevent uneven coating caused by air bubbles. The resin matrix was filled with an absorbent, which was a lightweight carbon-based carbon nanotube absorbent, with a content of 10 wt.% of the resin matrix.

[0069] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber and supported. In this embodiment, metal pads with a thickness of 1 cm are used for support. This ensures that the fabric maintains its three-dimensional shape after exiting the oven.

[0070] (4) Curing: The preform with the matrix solution evenly coated is placed in a DZ-2BCIV vacuum drying oven and dried at 70℃ for 10 hours to obtain a three-dimensional spacer fabric reinforced composite material. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are reversed to ensure that the resin content on the top and bottom surfaces is uniform. The composite material is then weighed and cut for testing.

[0071] (5) The volume fraction of the fiber in the prepared composite material is 55%. The reflectivity curve of the composite material in the 8-18 GHz range was tested using the bow method, as shown below. Figure 12 As shown, the reflection coefficient and absorption coefficient of the composite material when the front side faces upwards are as follows: Figure 13 As shown, the reflection coefficient and absorption coefficient of the composite material with the reverse side facing up are as follows: Figure 14 As shown, Γ-F represents the reflection coefficient when the reverse side is facing up, and AF represents the absorption coefficient when the reverse side is facing up.

[0072] Comparative Example 1

[0073] A three-dimensional spacer-reinforced composite material with a triangular cross-sectional shape was prepared. This example serves as a blank control sample.

[0074] (1) Quartz fiber is brittle and has poor abrasion resistance, making it prone to breakage when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller; instead, a guide thread is used as a medium to connect the quartz fiber to the guide thread, which in turn connects to the warp roller, preventing the warp yarns from breaking due to impact from the heddles. Since the woven structure is a three-dimensional spaced structure, with a larger yarn feed in the middle layer than in the upper and lower layers, the middle and upper warp yarns cannot use the same warp roller. By modifying the loom, two warp rollers were used, with their tension adjusted separately to ensure a three-dimensional effect in the woven structure. Secondly, humidification is necessary during weaving to reduce hairiness caused by friction from the reed and heddle holes. The woven sample size is 18cm × 18cm, with a triangular cross-section. This prefabricated body is entirely made of insulating quartz fiber.

[0075] (2) Preparation of epoxy resin matrix: Epoxy resin and curing agent are prepared in a ratio of 3:1. Stir with OS20-Pro stirrer for 180 minutes at room temperature. After they are evenly mixed, place them in a vacuum oven to remove air bubbles from the mixed solution and let them stand for 30 minutes to avoid uneven coating caused by air bubbles.

[0076] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber and then supported to ensure that the fabric retains its three-dimensional shape after exiting the oven.

[0077] (4) Curing treatment: The preform with the matrix solution evenly coated is placed in the DZ-2BCIV vacuum drying oven and dried at 70℃ for 10 hours. The desired composite material can be obtained. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are reversed to ensure that the resin content on the top and bottom surfaces is uniform. The composite material is then weighed and cut for testing.

[0078] (5) The volume fraction of the fiber in the prepared composite material is 50%. The reflectance curve of the composite material in the 8-18 GHz range was tested using the bow method, as shown in the figure. Figure 15 As shown, the reflection coefficient and absorption coefficient are as follows: Figure 16 As shown, Γ represents the reflection coefficient, and A represents the absorption coefficient.

[0079] Comparative Example 2

[0080] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared. It was a single layer with a spacing of less than 0.1 cm, set to 0.05 cm.

[0081] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, which in turn connects to the warp roller to prevent the warp yarn from breaking due to the impact force of the heddles. Since the weaving structure is a three-dimensional spaced structure, the middle layer has a larger yarn feed than the upper and lower layers. Therefore, the warp yarns of the middle layer and the upper and lower layers cannot use the same warp roller. Secondly, the humidity should be maintained at 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The size of the woven sample is 18cm×18cm, and the cross-sectional shape is one of triangle, rectangle or trapezoid. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The arrangement spacing is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.05cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.05cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 60°.

[0082] (2) Preparation of epoxy resin: The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model: ZTJ-03AB. The epoxy resin and matching curing agent were prepared in a ratio of 3:1. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After it was evenly mixed, it was placed in a vacuum oven to remove air bubbles from the mixture and allowed to stand for 30 minutes to avoid uneven coating caused by air bubbles.

[0083] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber and supported. In this embodiment, metal pads are used for support. The thickness of the metal pads is 1cm, so that the fabric maintains its three-dimensional shape after exiting the oven.

[0084] (4) Curing: The preform with the matrix solution evenly coated is placed in a DZ-2BCIV vacuum drying oven and dried at 70℃ for 10 hours to obtain a three-dimensional spacer fabric reinforced composite material. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are reversed to ensure that the resin content on the top and bottom surfaces is uniform. The composite material is then weighed and cut for testing.

[0085] (5) When the spacing between conductive fibers is less than 0.1cm, that is, there is no gap between conductive fibers, the reinforcement obtained by weaving under this condition is that the conductive fibers are close together to form a conductor, which will not absorb electromagnetic waves and will form total reflection.

[0086] Comparative Example 3

[0087] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared. It was a single layer with a spacing greater than 3.5 cm, set to 5.0 cm.

[0088] (1) Quartz fiber is brittle and has poor abrasion resistance. It is easy to break when knotted. During weaving, quartz fiber cannot be directly attached to the warp roller. Instead, a guide wire is used as a medium to connect the quartz fiber to the guide wire, which in turn connects to the warp roller to prevent the warp yarn from breaking due to the impact force of the heddles. Since the weaving structure is a three-dimensional spaced structure, the middle layer has a larger yarn feed than the upper and lower layers. Therefore, the warp yarns of the middle layer and the upper and lower layers cannot use the same warp roller. Secondly, the humidity should be maintained at 70-80% during the weaving process to reduce the increase of hairiness caused by the friction of the reed and heddle eye. The size of the woven sample is 18cm×18cm, and the cross-sectional shape is one of triangle, rectangle or trapezoid. When preparing the three-dimensional preform, the yarn is made of insulating quartz fiber and conductive carbon fiber mixed together. The conductive carbon fiber is arranged in a square with a side length of 2cm in the fabric. The fiber arrangement is as follows: In the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 5.0 cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 5.0 cm between adjacent conductive fiber yarns. The tilt angle between the core layer and the surface layer is 60°. The lower layer of the three-dimensional preform does not contain conductive carbon fibers. During testing, the side of the upper layer containing conductive carbon fibers facing upwards is defined as the front (Z), and the side of the lower layer without conductive carbon fibers facing upwards is defined as the back (F).

[0089] (2) Preparation of epoxy resin: The epoxy resin was purchased from Suzhou Wodawei Materials Technology Co., Ltd., model: ZTJ-03AB. The epoxy resin and matching curing agent were prepared in a ratio of 3:1. The mixture was stirred for 180 minutes at room temperature using an OS20-Pro stirrer. After it was evenly mixed, it was placed in a vacuum oven to remove air bubbles from the mixture and allowed to stand for 30 minutes to avoid uneven coating caused by air bubbles.

[0090] (3) Composite treatment of matrix resin and preform: The prepared matrix solution is evenly applied to the surface and interior of the preform fiber and supported. In this embodiment, metal pads are used for support. The thickness of the metal pads is 1cm, so that the fabric maintains its three-dimensional shape after exiting the oven.

[0091] (4) Curing: The preform with the matrix solution evenly coated is placed in a DZ-2BCIV vacuum drying oven and dried at 70℃ for 10 hours to obtain a three-dimensional spacer fabric reinforced composite material. During the curing process, 0.5 hours after the curing begins, the top and bottom surfaces of the composite material are reversed to ensure that the resin content on the top and bottom surfaces is uniform. The composite material is then weighed and cut for testing.

[0092] (5) When the spacing between conductive fibers is greater than 3.5 cm, the amount of conductive fibers in the reinforcement is too small, the conductive path formed in the fabric is too weak, and the reflection and absorption effect on electromagnetic waves is very weak, almost zero.

[0093] Comparative Example 4

[0094] A three-dimensional spacer fabric-reinforced composite material with a triangular cross-sectional shape and wave-absorbing properties was prepared. It was a single layer, and the tilt angle between the core layer and the surface layer was less than 30°, which was set to 15°.

[0095] If the angle between the core layer and the surface layer is too small, the fabric thickness will be difficult to achieve the set thickness, making it meaningless.

[0096] Comparative Example 5

[0097] In this embodiment, the tilt angle between the core layer and the surface layer is set to be greater than 90°, specifically 120°.

[0098] For example, in a triangle, what appears as a vertex from above and a side from below becomes a supplementary angle. Figure 17 The circles in the diagram represent weft yarn cross-sections, and the numbers inside the circles represent the number of weft yarns in one cycle. Therefore, the effect of a 120° tilt angle between the core layer and the surface layer is the same as that of a 60° tilt angle between the core layer and the surface layer.

[0099] The reflectivity curves of the composite materials measured in Examples 1-4 and Comparative Examples 1-5 at 8-18 GHz show that the three-dimensional prefabricated reinforced composite material with conductive fiber arrangement has a better wave absorption effect. Furthermore, the absorption coefficient curves show that the absorption coefficient of the composite material prepared in Comparative Example 3 is close to zero, while the absorption coefficients of the examples are all greater than those of the comparative examples. Therefore, the three-dimensional spacer fabric reinforced composite material with conductive fiber arrangement has better wave absorption performance.

[0100] The three-dimensional spacer fabric reinforced composite material prepared by this invention has the functions of load bearing and stealth. Therefore, it can be used as a structural and functional integrated composite material in the fields of defense, aerospace, transportation and electronics.

[0101] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0102] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing a three-dimensional spacer fabric-reinforced composite material, characterized in that, Specifically, the following steps are included: Weaving of three-dimensional preforms: Yarns are arranged in a regular pattern to produce three-dimensional preforms with different parameters and cross-sectional shapes; Curing: The resin matrix is ​​coated onto the three-dimensional preform and cured to obtain a three-dimensional spacer fabric reinforced composite material; In the weaving of the three-dimensional preform, the yarn is woven from a mixture of conductive fiber yarn and insulating fiber yarn; In the weaving of the three-dimensional preform, the parameters include: the width of the conductive fiber bundle, the spacing between the bundles, the direction of the bundles, the tilt angle between the core layer and the surface layer, and the number of layers of the three-dimensional preform. The width of the conductive fiber bundle is 0.1~3.5cm; The arrangement spacing is as follows: in the X direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1~3.5cm between adjacent conductive fiber yarns; in the Y direction, conductive fiber yarns and insulating fiber yarns are arranged alternately, with a spacing of 0.1~3.5cm between adjacent conductive fiber yarns. The arrangement direction is simultaneously arranged in the X and Y directions; The tilt angle between the core layer and the surface layer is 30~90°; The number of layers in the three-dimensional prefabricated body is 1 to 5; The cross-sectional shape is triangular, rectangular, or trapezoidal; During curing, the resin matrix is ​​filled with an absorbent, which is a lightweight carbon-based absorbent.

2. The three-dimensional spacer fabric reinforced composite material prepared by the preparation method according to claim 1.

3. The application of the three-dimensional spacer fabric reinforced composite material according to claim 2, characterized in that, Used in the manufacture of stealth components for military defense, aerospace, transportation, or electronic construction.

Citation Information

Patent Citations

  • Honeycomb three-dimensional integral woven structure type wave-absorbing composite material and preparation method thereof

    CN112625401A

  • A multi-functional fabric

    KR200227811Y1